(untitled) (Indian Journal of Animal Production and Management, 2013)
A survey on socio-economic characteristics and marketing attributes of Macherla Brown (local sheep) sheep farmers was conducted in Guntur, Nalgonda, Prakasam and Krishna districts of Andhra Pradesh with sample size of 104 farmers. The survey revealed the mean family size of the farmers was 4.34 with majority (80.77%) of famers belonged to medium size. About 57.7% of farmers had primary education. The overall mean land holding in the surveyed area was 1.94 ± 0.20 acres and 99.04% farmers chosen sheep husbandry as main occupation. Mean flock size was 120.64 ± 4.80 sheep and 41.34 % farmers had 50 to 100 sheep per flock. It was found that 60.58% sheep farmers realized their income from sale of meat. The sheep marketing pattern followed in the present study indicated that middlemen or butcher based (75.96%) market channel was very strong and followed by direct mode of marketing most of the farmers (64.42%) felt sheep rearing was remunerative enterprise.